Huaier Therapy for Successful Recovery of Cancer and Health Maintenance: Steady Progress and the End of Failed Promise - Tanaka, Manami; Tanaka, Tomoo; Teng, Fei; Lin, Hong; Li, Ning; Luo, Zhu; Sadahito, Sotaro; Suzuki, Toshiyuki; Wei, Ding; Lu, Zhengxin (Archives of Clinical and Biomedical Research, 2021)
The progress in cancer research has been processed by the discovery of molecules, genes, and mechanisms to cause carcinogenesis. Even with the advent of a novel technologies, the consequent drug discovery is still not enough to meet the demands, with the limited numbers of choice for anti-cancer strategy are not satisfactory. It is considered partly because mono-targeted agents should have certain limitations against diseases originated from multiple factors and environmental stresses throughout a life-long time. These defects in the current anti-cancer strategy of cancer therapy chiefly are caused by the lack of information required for cancer recovery. It is extremely required to obtain minimum-essential information to define the molecular basis for cancer recovery, with a comparison to that in the process of carcinogenesis. For this purpose, we should have successful agents possibly and reliably to cure the disease. We have identified anti-cancer effects of Huaier, and its unique characteristics of 1) no side effects or toxicity, 2) in dose dependent manner, 3) causing specific cancer cell death with simultaneous tissue regeneration, 4) miRNA-mediated transcriptional control on the rescue of multiple signal transduction, by dependent on individual genomic potential. Here we summarize the results of our genome scope project on clinical research of Huaier therapy on cancer patients. MEGA-DATA analysis in the process of cancer recovery by total RNA and small non-coding RNA sequencing. The results revealed significant differences in the behavior and coordination of RNA editing events, biomolecules, and multiple signaling pathways which beyond any speculations from the findings in the process of carcinogenesis. The time has come to change a point of view of “cancer therapy”, from the mere killing of cancer cells to regenerate the disrupted biophysiological functions through ageing and stress-accumulation in a l